BIOLOGICAL AGEING BASED ON PHYSICAL AND BIOCHEMICAL BIOMARKERS IN 0.5 MILLION U.K. BIOBANK PARTICIPANTS. (11th November 2018) - Chan, M; Arnold, M; Parish, S
Abstract: The biological processes that constitute ageing and lead to age-related disease risks are poorly understood. Improved knowledge of biomarkers that are indicators of ageing could highlight biological pathways where research should be focused, in order to identify modifiable risk factors and reduce risks currently attributed to chronological age. Previous studies have been limited in scale. Among 0.5 million participants aged 40–70 recruited into the UK Biobank between 2006–2010, we considered measurements for over 50 biomarkers describing physical and biochemical function, collected using touchscreen questionnaires, physical measurement devices, blood tests and urine tests. Linkage to electronic health records provided information on prior disease, and incidence of hospital-related outcomes and mortality for a median follow up duration of 6.0 years. The Klemera-Doubal method (recommended by previous studies) was used to derive a biological age by combining biomarkers strongly related to age, and was applied separately within each sex and by level of prior disease. In our ongoing research, worse lung function, lower fat-free body mass and lower bio-impedance metabolic rate emerge as strong risk factors of greater biological age. The effects of pre-preparation of biomarker measurements, such as adjusting for height or taking principle components, will be explored. We will discuss the predictive power of biological age for all-cause mortality and discharge to care homes, and the extent to which the predictive power of chronological age is captured by biological age and varies by prior disease.